Economic and legal provision of alternative taxation systems for legal entities - Panchyshyn, A.; Vlasova, Yа. (Економічний вісник Донбасу, 2024)
One of the main signs of the alternative tax system is its free choice by the taxpayer. It is the ability to choose independently a particular tax system of their choice, in this discretion is a sign of an alternative tax system. Alternative taxation systems are not seen as a tool to reduce taxpayers' tax burden. They are not a system of restrictions in the free choice of the taxation system, but serve as an incentive to ensure one or another result, in particular, which is an independent, free, alternative choice of the taxation system. Having examined the simplified system of taxation, accounting and reporting as an alternative to corporate income tax, it is noted that it was with the introduction of the simplified system of taxation that they began to really talk about the possibility of using alternative systems of taxation, which was expressed in the possibility of free choice of the conditions of tax legal relations. Однією з головних ознак альтернативної податкової системи є її вільний вибір платником податків. Саме можливість самостійно обирати ту чи іншу податкову систему за своїм вибором, на такий розсуд є ознакою альтернативної податкової системи. Альтернативні системи оподаткування не розглядаються як інструмент зменшення податкового навантаження платників податків. Вони не є системою обмежень у вільному виборі системи оподаткування, а слугують стимулом для забезпечення того чи іншого результату, зокрема, який є незалежним, вільним, альтернативним вибором системи оподаткування. Розглянувши спрощену систему оподаткування, обліку та звітності як альтернативу податку на прибуток підприємств, зазначається, що саме з введенням спрощеної системи оподаткування почали реально говорити про можливість використання альтернативних систем оподаткування, що виразилося в можливості вільного вибору умов податкових правовідносин.